Hubungan Karakteristik Pendampingan Desa dengan Tingkat Kinerja Pendampingan Desa dalam Program Pembangunan dan Pemberdayaan Masyarakat Desa (P3MD) di Kabupaten Pesawaran - Yulistiani, Ade; Gitosaputro, Sumaryo; Nikmatullah, Dewangga; Hassanudin, Tubagus; Rangga, Kordiyana K (Suluh Pembangunan : Journal of Extension and Development, 2025)
Development is an effort to realize the goals of the Republic of Indonesia as stated in the 1945 Constitution but are still not evenly distributed to all corners of Indonesia so that there is a need for village community assistance. This study aims to examine the performance of village assistants and analyze the relationship between village assistant features and assistant performance. Analysis of the data used using descriptive quantitative. The population in this research is Village Empowerment Facilitators (PDP) Local Village Facilitators (PLD). Respondents to this study were 59 village officials and 1 expert to assess the performance of 16 Empowerment Village Facilitators (PDP) and 28 Local Village Facilitators (PLD). Data collection...was carried out in August 2021. The data analysis method used was was usin Rank Spearman correlation analysis to find out variables...related to the performance of village assistants. The results of the study show that the performance of PLD in Pesawaran District in the implementation of P3MD is in the high category and the performance of PDP in Pesawaran Regency is in the medium category. support from PLD. The level of non-formal education, the level of work discipline, the number of attenuation villages, the distance where the companion lives and the companion's interpersonal relationship are significantly related to the performance of the village assistant in Pesawaran District. Keywords: Performance, Empowerment, Village Facilitator